An Extension and Moderational Analysis of the Family Stress Model Focusing on African American Adolescents. Issue 2 (April 2015) - Landers‐Potts, Melissa A.; Wickrama, K. A. S.; Simons, Leslie Gordon; Cutrona, Carolyn; Gibbons, Frederick X.; Simons, Ronald L.; Conger, Rand
Abstract : This study focuses on 422 African American families with two caregivers as children transition into adolescence. The family stress model was tested longitudinally using structural equation modeling. Results showed that economic stress was associated with economic pressure and depressive symptoms among caregivers, which in turn was related to caregiver conflict. Higher levels of conflict had a negative influence on parenting quality at Wave 2, and this was linked to adolescent functioning. The depressive symptomology of secondary caregivers (SCs) exerted a greater indirect effect in the models than that of primary caregivers (PCs) and had a direct relationship to adolescent's positive adjustment. Moderational effects of caregiver conflict on the link between economic pressure/adolescent outcomes and economic pressure/hostile parenting were also tested. The case for the importance of including PCs and SCs of children and adolescents in future research focusing on African American families facing economic hardship is made.